KEEFEKTIFAN MODEL PERMAINAN BOY-BOYAN TERHADAP HASIL BELAJAR TEMA “DIRIKU” SISWA KELAS I SD - Anggraini, Cicilia Clara Devi; Untari, Mei Fita Asri (Mimbar Sekolah Dasar, 2014)
This research is motivated by the importance of integrated thematic learning curriculum themes and 2013 by using the model of traditional games as learning a fun, active, effective and meaningful for students. There are many students who believe that learning in school was just learning in the classroom rigid and monotonous so that students difficult to understand the concept of the teacher taught the material that causes the results low student learning and learning becomes ineffective. Purpose of this study was to determine the effectiveness of the existing models in the game Boy-Boyan integrated thematic learning on learning outcomes theme of "Me". Based on the analysis of data obtained by the price of hypothesis testing tcount 8078 and amounted to 2,021 t table. Because of tcound t table or 8,078 2,021 then Ho is rejected or it can be said that the difference in average initial conditions to the final conditions significantly. The conclusions is there is effectivenes of the models Boy-boyan games in integrated thematic learning in learning outcomes theme of "me" grade 1 SDN Pandeanlamper 5 Semarang.Keywords: boy-boyan game model, the result of studying the theme of “me”.